Aksi Mitigasi Risiko Rantai Pasok Gula Rafinasi Dengan Menggunakan Cartesian Diagram - ulfah, Maria (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2017)
Study on risk in supply chain has become an important topic due to increasing variety and level of risk faced by the supply chain. Consumer complain related to this issue is increasing through the years. Risk management of refine sugar supply chain in this research use House of Risk (HOR) model, consist of HOR 1 and HOR 2. Identification, analysis, and risk evaluation was using HOR 1, while risk treatment or mitigation action was using HOR 2. Risk identification and risk cause was based on Suply Chain Operations Reference (SCOR) which consist of five dimension namely plan, source, make, deliver, and return. Risk analysis was using Failure Mode and Effects Analysis (FMEA). From the analysis of each quadrant, the responses of the companys’s management is to more realize the mitigation actions that are in quadrant 2 because it has a high level effectiveness and has a high level of ease also to be realized. It can be concluded by the Cartesian diagram in quadrant 2, mitigation action priority for realization is annual shutdown/maintenance, 1-year contract with the customers, and preparing the buffer stocks.